ANALISIS UNSUR INTRINSIK NOVEL"SERENDIPITY" KARYA ERISCA FEBRIANI MENGGUNAKAN PENDEKATAN OBJEKTIF - Selvia Ardianti; Tajuddin (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
This study aims to analyze the intrinsic elements in the novel "Serendipity" by Erisca Febriani using an objective approach. The technique used in the research used in this analysis uses descriptive qualitative techniques. The resource in this research is the novel "Serendipity" by Erisca Febriani. The data collection method used in this research is to read critically and thoroughly the contents of the novel. As for the technique of research results that can put forward the intrinsic elements in the form of: theme, character, plot, setting, language style, and message.